Which of the following should be done to both sides of the equation −6x=48 to solve the value of x ?(1 point) Responses divide by −6 divide by negative 6 add 6 add 6 divide by 6 divide by 6 multiply by −6
11 answers
To solve the value of x in the equation −6x = 48, you should divide both sides of the equation by -6.
Which of the following should be done to both sides of the equation x12=6 to solve the value of x?(1 point) Responses multiply by −12 multiply by negative 12 divide by 12 divide by 12 multiply by 12 multiply by 12 multiply by 6
To solve the value of x in the equation x12 = 6, you should divide both sides of the equation by 12.
Which of the following should be done to both sides of the equation x12=6 to solve the value of x ?(1 point) Responses multiply by −12 multiply by negative 12 divide by 12 divide by 12 multiply by 12 multiply by 12 multiply by 6
To solve the value of x in the equation x12 = 6, you should divide both sides of the equation by 12.
What is the solution of the equation 52x = −18 ?(1 point) Responses −20 negative 20 120 Start Fraction 1 over 20 End Fraction −516 negative Start Fraction 5 over 16 End Fraction −120
To find the solution of the equation 52x = −18, you should divide both sides by 52.
The solution is x = -18/52 or x = -9/26.
The solution is x = -18/52 or x = -9/26.
What is the solution of the equation 5/2x=-1/8
To solve the equation (5/2)x = -1/8, you should divide both sides of the equation by 5/2:
[(5/2)x] / (5/2) = (-1/8) / (5/2)
x = (-1/8) / (5/2)
Now, to divide a fraction by another fraction, you multiply by the reciprocal of the second fraction:
x = (-1/8) * (2/5)
x = (-1 * 2)/(8 * 5)
x = -2/40
x = -1/20
Therefore, the solution to the equation is x = -1/20.
[(5/2)x] / (5/2) = (-1/8) / (5/2)
x = (-1/8) / (5/2)
Now, to divide a fraction by another fraction, you multiply by the reciprocal of the second fraction:
x = (-1/8) * (2/5)
x = (-1 * 2)/(8 * 5)
x = -2/40
x = -1/20
Therefore, the solution to the equation is x = -1/20.
what is the solution of the equation -x/2.9=-3?
To solve the equation -x/2.9 = -3, you can multiply both sides of the equation by 2.9 to eliminate the fraction:
2.9 * (-x/2.9) = 2.9 * (-3)
Simplifying, we have:
-x = -8.7
Now, to solve for x, we can isolate the variable by multiplying both sides of the equation by -1:
(-1) * (-x) = (-1) * (-8.7)
x = 8.7
Therefore, the solution to the equation is x = 8.7.
2.9 * (-x/2.9) = 2.9 * (-3)
Simplifying, we have:
-x = -8.7
Now, to solve for x, we can isolate the variable by multiplying both sides of the equation by -1:
(-1) * (-x) = (-1) * (-8.7)
x = 8.7
Therefore, the solution to the equation is x = 8.7.